Adsorption Capability of Lead, Nickel and Zinc by Exopolysaccharide and Dried Cell of Ensifer meliloti - Lakzian, Amir; R. Berenji, Ali; Karimi, Esmael; Razavi, Solmaz (Asian Journal of Chemistry, 2010)
In this study, the adsorption capability of lead, nickel and zinc by exopolysaccharide (EPS) and dried cell of Ensifer meliloti (formerly Sinorhizobium meliloti) which nodulates alfalfa has been investigated. The results showed that dried cells had less adsorbing tendency compared to EPS of Ensifer meliloti MS-125. 0.02 g of EPS adsorbed 89, 85 and 66 % of lead, nickel and zinc, respectively, presented in 50 mg L-1 solutions. Maximum adsorption of lead, nickel and zinc were 110, 54 and 94 mg g-1 EPS, respectively, estimated by using Langmuir model.